Pengaruh Penerapan Sistem Operasional Digitalisasi Perbankan Syariah Terhadap Kinerja Karyawan Dalam Peningkatan Kualitas SDM - Hamidah, Metha Nur; Putra, Purnama (At-Tamwil: Journal of Islamic Economics and Finance, 2024)
The researchs aims to analyze the effect of the digitalization operational system on employee performance in improving the quality of human resources at Bank Syariah Indonesia. The sample in this study was taken based on the population of employees at Islamic Banks totaling 3,493 employees using purposive sampling technique with a sample of 97 employees. The data processing method uses multiple regression methods with statistical tests first. Statistical tests consist of t test, f test, coefficient of determination (R2). The analysis technique in this study is path analysis which aims to calculate the effect of one or more independent variables on other dependent variables. The results showed that the value of the digitalization operational system had a positive effect on employee performance and the digitalization operational system, employee performance had an effect on improving the quality of human resources.